A lifestyle-based needs assessment of two European communities prior to the development and deployment of a digital health coaching smartphone application - Iglesias-Cans, Marina; Loughnane, Croia; O’Donovan, Roisin; Iftimoaei, Ciprian; Vasiliu, Diana; Iftimoaei, Manuela; Enache, Ingrid; Achitei, Angela; Dunne, Padraic J. (Frontiers in Public Health, 2025)
IntroductionThere is growing interest and demand for leveraging digital technology to enhance the reach and scalability of health and wellbeing interventions, as a solution to the global burden of noncommunicable diseases. For positive health sciences, digital technology has been identified as a feasible solution to increasing the accessibility, scalability and reach of positive health interventions. While digital health solutions have the potential to improve the health and wellbeing of communities and reduce the burden on health systems, these solutions often take a one-size-fits-all approach in their design and implementation. This study aimed to conduct a Community-Based Participatory Research (CBPR) informed needs assessment in Athy (Ireland) and Iași (Romania) to identify lifestyle-related health challenges, barriers, and digital engagement preferences in preparation for implementing the Connect5 digital health coaching intervention.MethodsA mixed-methods cross-sectional design was employed, involving quantitative surveys (n = 219 in Ireland; n = 205 in Romania) and qualitative interviews/focus groups. Surveys assessed sociodemographic characteristics, lifestyle habits, barriers, support needs, and digital health perspectives.ResultsBoth communities reported challenges with sleep, physical activity, sedentary behavior, and stress, with common barriers including lack of time (due to work/study/childcare) and the high cost of healthy food. Notable variations in lifestyle needs, barriers, and support preferences were observed across sociodemographic groups within each community, including gender, age, education, and residency. Lower socioeconomic groups faced more systemic barriers like high food costs or lack of safe outdoor spaces. Despite different levels of prior engagement with digital solutions, both communities showed strong interest in digital health coaching solutions.DiscussionThe findings from this needs assessment will inform the design and implementation of the upcoming Connect5 project and provide broader insights for future digital health initiatives. They highlight the importance of integrating community voices and sociodemographic insights to ensure that digital health solutions are relevant, inclusive, and equitable, ultimately promoting sustained engagement, reducing health disparities, and improving population wellbeing.